Carol II of Romania, a controversial king (Confluenţe Bibliologice, 2022)
This article reveals the importance of the monumental work Charles II of Romania. A controversial king, author Narcis Dorin Ion, Director of the Peles National Museum, dedicated to King Carol II, the last sovereign of Greater Romania. Through a search in several archives, the author finally managed to edit 5 volumes, which he illustrated with an impressive number of images. The five volumes add up to almost 2,500 truly impressive pages through the quality of historical information, the beauty of the discourse, the perfect concordance between the text and the iconographic material that accompanies it.
Keywords: historical personality; Romanian history